2016
DOI: 10.1080/15222055.2016.1159629
|View full text |Cite
|
Sign up to set email alerts
|

Structural Complexity Improves the Rearing Performance of Rainbow Trout in Circular Tanks

Abstract: While structural complexity has been used extensively during hatchery rearing in an attempt to improve poststocking survival, the potential impact of this complexity on hatchery rearing performance has largely been ignored. This study examined the growth and condition of juvenile Rainbow Trout Oncorhynchus mykiss reared in nearly fully covered circular tanks containing nine vertically oriented round aluminum rods (structurally complex) compared with that of trout reared in almost fully covered tanks with no ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
61
5

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 37 publications
(83 citation statements)
references
References 30 publications
17
61
5
Order By: Relevance
“…These results are similar to Brockmark et al [9], who found no significant difference in fish rearing performance with the addition of plastic plants and rocks to tank bottoms. Although neither this study nor Brockmark et al [9] found significant benefit with the use of environmental enrichment, benefits from the addition of structure in tanks has been found in other studies [2,6]. One difference that could account for the significant results of Kientz and Barnes [6] is the placement of structure in the tank.…”
Section: Discussioncontrasting
confidence: 51%
See 4 more Smart Citations
“…These results are similar to Brockmark et al [9], who found no significant difference in fish rearing performance with the addition of plastic plants and rocks to tank bottoms. Although neither this study nor Brockmark et al [9] found significant benefit with the use of environmental enrichment, benefits from the addition of structure in tanks has been found in other studies [2,6]. One difference that could account for the significant results of Kientz and Barnes [6] is the placement of structure in the tank.…”
Section: Discussioncontrasting
confidence: 51%
“…Although neither this study nor Brockmark et al [9] found significant benefit with the use of environmental enrichment, benefits from the addition of structure in tanks has been found in other studies [2,6]. One difference that could account for the significant results of Kientz and Barnes [6] is the placement of structure in the tank. Both this study and Brockmark et al [9] added structure to the tank floor while Kientz and Barnes [6] suspended structure from tank covers.…”
Section: Discussioncontrasting
confidence: 51%
See 3 more Smart Citations